Roles of YUCCAs in auxin biosynthesis and drought stress responses in plants - Cheol Park, Hyeong (Landes Bioscience, 2013)
Auxin, a plant hormone, plays crucial roles in diverse aspects of plant growth and development reacting to and integrating environmental stimuli. Indole-3-acetic acid (IAA) is the major plant auxin that is synthesized by members of the YUCCA (YUC) family of flavin monooxygenases that catalyse a rate-limiting step. Although the paths to IAA biosynthesis are characterized in Arabidopsis, little is known about the corresponding components in potato. Recently, we isolated eight putative StYUC (Solanum tuberosum YUCCA) genes and five putative tryptophan aminotransferase genes in comparison to those found in Arabidopsis.(1) The specific domains of YUC proteins were well conserved in all StYUC amino acid sequences. Transgenic potato (Solanum tuberosum cv. Jowon) overexpressing AtYUC6 showed high-auxin and enhanced drought tolerance phenotypes. The transgenic potatoes also exhibited reduced levels of ROS (reactive oxygen species) compared to control plants. We therefore propose that YUCCA and TAA families in potato would function in the auxin biosynthesis. The overexpression of AtYUC6 in potato establishes enhanced drought tolerance through regulated ROS homeostasis.